A modified asphalt particle enhanced oil-based foam system and its preparation method and application

By using fluorinated acrylic acid copolymer and modified asphalt particles in a tight oil reservoir, the problems of gas traversing and asphaltene precipitation during CO2 throughput are solved, and higher recovery rates and lower asphaltene deposition amounts are achieved.

CN119039728BActive Publication Date: 2025-03-07CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411137929.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-03-07
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The prior art has problems of gas traversing and asphaltene precipitation in CO2 throughput in tight oil reservoirs, resulting in low recovery and fast decreasing capacity.

Method used

The oil-based foam system prepared by fluorinated acrylic acid copolymer and modified asphalt particles is used to reduce the interface tension through the coordinated adsorption of fluorinated acrylic acid copolymer and modified asphalt particles at the oil and gas interface, and the modified substances of the modified asphalt particles are diffused and transferred to the asphalt precipitated in the formation to achieve in situ modification of the asphaltene in the formation.

Benefits of technology

The gas traversal flow is effectively controlled, the foam traversal validity period is extended, the recovery rate is improved, and the amount of asphaltene deposited in the final output oil is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039728B_ABST
    Figure CN119039728B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas field development, specifically a modified asphalt particle enhanced oil-based foam system and a preparation method and application thereof, wherein the asphalt enhanced oil-based foam system comprises a fluorinated acrylic copolymer, modified asphalt particles and a mixed oil solvent in a mass ratio range of (1-2):(0.2-1):100; the foaming ratio of the foam system is 325%-355%, and the defoaming half-life is 61min-90min. Fluorinated acrylic copolymer and modified asphalt particles are selected, and the synergistic adsorption of the two at the oil-gas interface is utilized to effectively control the interfacial tension, and at the same time, the prepared foam has good foaming property and stability, thereby effectively controlling gas cross-flow; the modified substance on the surface of the modified asphalt particles is diffused and transferred to the surface of the asphaltene precipitated from the stratum, realizing the in-situ modification of the stratum asphaltene, so that it is retained in the core and continues to play the role of stabilizing the foam, thereby reducing the asphaltene deposition amount in the final output oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas field development, in particular to a modified asphalt particle enhanced oil-based foam system and a preparation method and application thereof. Background Art

[0002] The oil reservoirs to be developed include a large number of tight oil reservoirs, which are characterized by permeability usually less than 1×10 -3 μm, the lithology is mainly sandstone, carbonate rock and shale, generally there is no natural production capacity or industrial production capacity, and large-scale horizontal well fracturing is required for production. The exhaustion-type development of tight oil has a rapid capacity decline rate and low recovery rate, and it is often necessary to supplement the formation energy by water injection or gas injection. Among them, CO2 huff and puff is one of the effective means to improve the recovery rate of tight oil reservoirs in recent years. However, it also has the problem of gas channeling. When the gas flows rapidly, the energy is released quickly. After multiple huff and puff cycles, the ability to carry crude oil production decreases rapidly, and the energy supplement effect is poor or even ineffective, resulting in a low final recovery rate. Foam has a good effect of blocking gas channeling, and can be used in the process of gas huff and puff to achieve continuous release of formation energy, slow down the rate of capacity decline, and improve the final recovery rate.

[0003] When oil-based foam is used, it can be injected in the form of alternating gas-surfactant solvent plugs. Small segments of solvent plugs carry oil-soluble surfactants or other additives into the formation and mix with the formation crude oil after contact. In the production process of gas throughput, the presence of surfactants can form oil-based foam to block gas crossflow, achieve slow release of gas energy, and improve recovery. However, at present, due to the low interfacial tension (surface tension = 15-30mN·m) of oil-phase solvents (including various hydrocarbon finished oils and crude oil) compared to conventional water-phase solvents, -1 ) and low dielectric constant (dielectric constant = 2-3), resulting in the difficulty of foaming and the instability of the system. Therefore, it is urgent to develop oil-based foams with better performance to meet actual needs.

[0004] Chinese patent document CN 108071390 A (application number 201810018800.4) provides an oil-soluble foaming agent enhanced mixed gas throughput experimental device and its application method suitable for complex heavy oil reservoirs. The oil-soluble foaming agent is used with a mixed gas of natural gas and propane to form artificial foam oil to reduce the gas output rate and slow down the energy release, achieving good results. However, the gas used is a mixed gas of natural gas and propane, which is prone to combustion or explosion and has certain safety hazards. It is only suitable for experiments under laboratory conditions and cannot be widely used in actual reservoir construction.

[0005] Chinese patent document CN 114437683 A (application number 202011210615.9) provides an oil-based foam system in which the foaming agent is a compound of a fluorocarbon cationic surfactant and a methyl silicone surfactant, which can effectively reduce the oil-gas interfacial tension and improve the foaming performance of the oil-based foam. However, the fluorocarbon surfactant used in this system is a cationic type with positive charge, while the formation is negatively charged, and there is a lot of adsorption loss when injected into the formation, which limits its large-scale application in oil fields.

[0006] In addition, Chinese patent documents CN 108671850 A (application number 201810445643.5), CN 108690592 A (application number 201810445586.0) and CN 108690593 A (application number 201810445624.2) respectively disclose fluorinated octyl-containing fluorosilicone surfactants and their synthesis methods, which improve the foam stabilization performance in the oil phase solvent by introducing fluorine atoms and silicon atoms simultaneously in one surfactant molecule. However, the number of fluorine atoms in a single molecule of the above surfactants is 17. It is well known in the art that when the number of fluorine atoms in a single molecule exceeds 6, biological toxicity exists. The surfactants provided by the above patents are all highly biologically toxic and cause certain pollution to the environment. At the same time, the water phase is introduced into the foam system provided by the above patents, and the oil-water emulsion foam formed needs to be demulsified and separated.

[0007] For tight oil reservoirs, especially when the asphaltene content of crude oil in tight oil reservoirs is relatively high, the above-mentioned system or scheme is likely to lead to a high amount of formation asphaltene precipitation during the CO2 huff and puff process, damaging the formation and resulting in a short huff and puff cycle and a rapid decline in production. Currently, there is a lack of a system that can simultaneously solve the problems of gas crossflow and asphaltene precipitation during the CO2 huff and puff process in tight oil reservoirs. Summary of the invention

[0008] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a modified asphalt particle enhanced oil-based foam system and a preparation method and application thereof. Fluorinated acrylic copolymer and modified asphalt particles are selected and their synergistic adsorption effect at the oil-gas interface is utilized to effectively control the interfacial tension, while making the prepared foam have good foaming and stability, thereby effectively controlling gas cross-flow. At the same time, the modified substance on the surface of the modified asphalt particles is diffused and transferred to the surface of the asphaltene precipitated from the formation, thereby realizing the in-situ modification of the formation asphaltene, so that it remains in the core and continues to play a role in stabilizing the foam, thereby reducing the amount of asphaltene deposition in the final produced oil.

[0009] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0010] A modified asphalt particle enhanced oil-based foam system, comprising a fluorinated acrylic copolymer, modified asphalt particles and a mixed oil solvent, wherein the mass ratio of the fluorinated acrylic copolymer, the modified asphalt particles and the mixed oil solvent is in the range of (1-2):(0.2-1):100;

[0011] The structural formula of fluorinated acrylic copolymer is as follows:

[0012]

[0013] In formula I, x is 3-6, y is 15-20;

[0014] Modified asphalt particles are prepared by the following method:

[0015] After the petroleum asphalt is made into particles with a particle size of 500-700 mesh, a modifier, an interface dispersant, a charge stabilizer and a flexibility regulator are added by spraying, and after stirring at a speed of 20rpm-40rpm for 6-8h, the modified asphalt particles are obtained by standing and drying for 24h; the dosage of the modifier, the interface dispersant, the charge stabilizer and the flexibility regulator is 5wt%-10wt%, 10wt%-20wt%, 2wt%-5wt% and 5wt%-10wt% of the mass of the petroleum asphalt respectively;

[0016] The foaming ratio of the foam system is 325%-355%, and the defoaming half-life is 61min-90min.

[0017] Compared with water-based foam, oil-based foam has the following advantages in plugging gas crossflow: (1) Oil-based foam uses hydrocarbon solvents as the base liquid for foaming, so there is no problem of water-based foam defoaming when it encounters oil, resulting in a weakened sealing effect. It can maintain stability for a long time under the reservoir environment, thereby increasing the scope of the sealing effect; (2) The surface properties of chemical additives such as oil-soluble surfactants or particles in the oil-based foam system are all oleophilic, which can enter the reservoir more easily and with lower loss; (3) Oil-based foam is regenerable when it encounters oil in the reservoir, and there is no problem of water-based foam "defoaming when it encounters oil"; even if the injected oil-based foam decays and defoams, new foam will be generated in the crude oil due to the presence of surfactants such as foaming agents; (4) Oil-based foam is more likely to form a continuous and homogeneous foam oil flow in the formation, which can be released slowly and evenly, ensuring that the energy brought by the gas can be released slowly and evenly during the "exhalation" process of gas throughput, giving full play to the energy-enhancing and recovery-enhancing effect of gas throughput, and better improving the CO2 oil exchange rate.

[0018] The oil-based foam system provided by the present invention uses a fluorinated acrylic copolymer as a surfactant. Compared with conventional surfactants, the fluorine element has a high electronegativity, a high oxidation potential, and a high ionization energy. This characteristic makes the CF bond energy high, so the CF structure is much more stable than the CH structure; in addition, fluorine atoms are very difficult to polarize, making the CF bond polarity smaller than the CH bond. It is precisely because of this low polarity that the hydrophobic effect of the fluorocarbon chain is much stronger than that of the hydrocarbon chain, and the low polarity makes the fluorocarbon chain both hydrophobic and oleophobic; in addition, the low polarity leads to weak interaction between the fluorocarbon chains themselves. The combined effect of these two factors makes the fluorocarbon surfactant molecules have a stronger tendency to leave the liquid phase in the solution than other surfactant molecules, and they are oriented and aggregated to form molecular films on the interface, so that they have different interfacial tension reduction characteristics from conventional surfactants.

[0019] Fluorinated acrylic copolymers have fluorinated and non-fluorinated segments, of which the fluorinated segments are short, with x values ​​of 3-6, and are non-biotoxic. Due to the oleophobic properties of the CF bond, they are good air-philic heads; the non-fluorinated hydrocarbon segments are long, with y values ​​of 15-20, and are highly non-polar, and have good affinity with oil phase solvents. If the non-fluorinated hydrocarbon chain is too short, the surfactant will have insufficient lipophilicity, and if it is too long, the by-products will increase during the synthesis process, increasing the cost. In addition to the O atom in the -COOH functional group, which can be a hydrogen bond acceptor, the F atom has a greater electronegativity and the strongest electron-accepting ability among all hydrogen bond acceptor atoms. The FH···F formed by it is the strongest hydrogen bond. The main component of asphalt particles is asphaltene, and the main structure of asphaltene is polycyclic aromatic groups. In addition, it also has more heteroatom structures, such as N, O, and S. In the heteroatom functional groups of asphaltene molecules, the H atoms bonded to the heteroatoms act as H bond donors. The hydrogen bond acceptor is provided by the fluorinated acrylic copolymer surfactant, and the hydrogen bond donor is provided by the petroleum asphaltene, and the two interact through hydrogen bonds to exert a synergistic effect. The total adsorption amount on the interface is increased, the interface arrangement is more compact, and a liquid film with lower interfacial tension and higher tensile strength can be formed, so that the asphaltene and fluorocarbon surfactants can strengthen the oil-based foam surface with better anti-disturbance ability. At the same time, the hydrogen bond interaction between the two is in a competitive relationship with the aggregation effect of asphaltene in the bulk phase, which can effectively curb the aggregation behavior of asphaltene molecules in the bulk phase to form irregular aggregates, thereby achieving a certain uniform dispersion effect, slowing down the thinning of the liquid film, and further improving the stability of the foam system.

[0020] Compared with asphalt particles or existing modified asphalt particles, the modified asphalt particles have the following beneficial effects after being treated with modifiers, interfacial dispersants, charge stabilizers and flexibility regulators: the lipophilic and airphilic abilities of the particle surface are balanced, and the ammonium groups grafted on the surface can further strengthen the H-bond effect between the particles and the fluorinated acrylic copolymer, strengthen synergistic adsorption, and can be well adsorbed on the oil-gas interface; the agglomeration ability of the particles is weakened, and they can be well dispersed in the oil phase; the surface charge is relatively balanced, and the surface is electrically neutral as a whole, and it is not easy to be adsorbed by the formation and cause loss; the particle's flexibility and deformation ability is enhanced, and it is not easy to be blocked when passing through pores and cracks. After the modified asphalt particles are injected into the formation with the foam, the modifier, interfacial dispersant, charge stabilizer and flexibility regulator will transfer and diffuse to the asphaltene precipitated from the formation, thereby modifying the asphaltene seeping out of the formation, preventing the formation from being blocked, and also realizing the in-situ supplementation of the modified asphalt particles in the formation, effectively extending the effective period of the foam sealing.

[0021] Preferably, the mass of the fluorinated acrylic copolymer is twice the mass of the modified asphalt particles.

[0022] Preferably, the modifier is a cationic quaternary ammonium surfactant; more preferably, the modifier is selected from at least one of dodecyl trimethyl ammonium salt, didodecyl trimethyl ammonium salt or dodecyl dimethyl benzyl ammonium salt. The function of the modifier is to adjust the surface lipophilicity and airphilicity balance of the asphalt particles and enhance the interface adsorption.

[0023] Preferably, the interfacial dispersant is selected from non-ionic amino surfactants and / or cationic diquaternary ammonium surfactants, and is used to improve the interfacial adsorption performance of asphalt particles and promote particle dispersion.

[0024] Further preferably, the nonionic amino surfactant is bisaminoethylaminomethyl-p-alkylphenol, and its structural formula is as follows:

[0025]

[0026] In formula II, R1 is a C4-C8 straight chain alkyl group;

[0027] The structural formula of cationic diquaternary ammonium salt surfactant is as follows:

[0028]

[0029] In Formula III, R2, R3, R4, and R5 are C1-C3 straight chain alkyl groups; R6 and R7 are C6-C 12 A straight chain alkyl group; Z - For halogen ions or PO3 - Any of .

[0030] Preferably, the charge stabilizer is ethylenediaminetetraacetic acid, the purpose of which is to adjust the charge adsorption balance on the surface of the asphalt particles.

[0031] Preferably, the flexibility regulator is an oil-soluble resin; preferably at least one of polypropylene, polycarbonate or polyetheretherketone, the purpose of which is to enhance the flexible deformation ability of the asphalt particles.

[0032] Preferably, the mixed oil solvent is composed of light oil and tight oil, the light oil is selected from kerosene or diesel, and the ratio of light oil to tight oil is 1:(4-9); further preferably, the surface density of tight oil is 0.83-0.88 g / cm 3 , the viscosity is not higher than 5mPa·s. The mixed oil can dissolve oil-soluble surfactants and suspend modified asphalt particles, while simulating the actual oil phase composition of the light oil plug in contact with tight oil after being injected into the formation.

[0033] The feed ratio of fluorinated acrylic copolymer and modified asphalt particles is set within the above-mentioned dosage range; the fluorinated acrylic copolymer and the modified asphalt particles are linked by hydrogen bonding at a ratio of 1:0.5. During the hydrogen bonding process, the modified asphalt particles will also undergo spontaneous disordered self-assembly aggregation behavior. The hydrogen bonding and disordered self-assembly aggregation behaviors are in a dynamic equilibrium state.

[0034] The present invention also provides a method for preparing the modified asphalt particle enhanced oil-based foam system, comprising the following steps:

[0035] S1. Adding modified asphalt particles into light oil and stirring for the first time, adding dense oil for the second stirring and ultrasonic dispersion to obtain a modified asphalt particle suspension;

[0036] S2. Add the fluorinated acrylic copolymer to the modified asphalt particle suspension, and stir at a low speed to obtain a composite solution;

[0037] S3. In a CO2 / N2 / deoxygenated air atmosphere, the compound solution is stirred at high speed to obtain a modified asphalt particle-enhanced oil-based foam system.

[0038] Preferably, in step S1, the first stirring condition is stirring at a rotation speed of 1000 rpm for 0.5 h-1 h; the second stirring condition is stirring at a rotation speed of 1000 rpm for 1 h-1.5 h.

[0039] Preferably, in step S1, the ultrasonic dispersion condition is intermittent dispersion at a power of 600W-800W for 1.5h-2h, and the intermittent dispersion process is cyclically carried out in the order of dispersion-intermittence, wherein the dispersion time is 3min-5min and the intermittent time is 40s-60s.

[0040] Preferably, in step S2, the low-speed stirring condition is stirring at a rotation speed of 600 rpm for 0.5 h-1 h.

[0041] Preferably, in step S3, the high-speed stirring condition is stirring at a speed of 8000 rpm for 3 min-5 min.

[0042] The present invention also provides the use of the modified asphalt particle enhanced oil-based foam system or the modified asphalt particle enhanced oil-based foam system prepared by the above preparation method in gas throughput in tight oil reservoirs.

[0043] Preferably, in the application, the asphaltene content of the crude oil in the tight oil reservoir is in the range of 3.5 wt% to 6.0 wt%.

[0044] Preferably, in the application, the method for gas throughput in tight oil reservoirs is as follows:

[0045] (1) Injecting the modified asphalt particle enhanced oil-based foam system at an injection volume of 0.05 PV and an injection pressure 0.5-1 MPa higher than the average core pressure, and injecting gas at an injection volume of 0.20 PV and an injection pressure 2-3 MPa higher than the average core pressure;

[0046] (2) Waiting for the core pressure to stabilize before reducing the pressure for production. The gas released from the tight oil forms modified asphalt particles to strengthen the oil-based foam under the action of the foaming agent solution.

[0047] (3) Repeat steps (1) to (2) for multiple rounds of gas throughput until the throughput cycle recovery factor is lower than the economic production recovery factor by 2.5%.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] 1. The present invention uses a reinforced oil-based foam system prepared by using modified asphalt particles and fluorinated acrylic copolymer. The fluorinated acrylic copolymer and the modified asphalt particles are interconnected by hydrogen bonds, so that the interfacial adsorption amount is improved. The modified asphalt particles are linked to the long molecular chain of the fluorinated acrylic copolymer by hydrogen bonds, so that they can be stably arranged on the interface, the interfacial tension is significantly reduced, and the foam liquid film strength is significantly improved.

[0050] 2. After the modified asphalt particles are modified, their oil- and gas-affinity is balanced, and the adsorption capacity on the interface is increased; in addition, the charge on the particle surface is relatively balanced and electrically neutral, and it is not easy to be adsorbed by the formation and cause loss; at the same time, the particles are also softened and modified, and have flexible deformation characteristics under the high temperature and high pressure conditions of the reservoir. After being squeezed and deformed, they can pass through the pore throats and will not block the formation. The modified asphalt particles have achieved multi-performance integration and can better adapt to the complex tight oil reservoir conditions.

[0051] 3. The modifiers, interfacial dispersants, charge stabilizers and flexibility regulators grafted on the surface of the modified asphalt particles will be transferred and diffused to the asphaltene precipitated from the formation. While modifying the formation asphaltene to prevent clogging of the formation, it also realizes the in-situ supplementation of the modified asphalt particles in the formation, ultimately extending the effectiveness of the foam sealing.

[0052] 4. The enhanced oil-based foam system used in the present invention has high foam stability. In the process of gas throughput in tight oil reservoirs, it can more effectively block gas cross-flow, slow down the release of gas energy, increase oil efficiency, and ultimately increase the recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a graph of core pressure changes during the first five cycles of the CO2 gas injection process assisted by the modified asphalt particle-enhanced oil-based foam system in Example 2 of Experimental Example 2.

[0054] Figure 2 This is a graph showing the core pressure changes during the first five cycles of the CO2 gas injection process assisted by the oil-based foam system in Comparative Example 1 in Experimental Example 2.

[0055] Figure 3 This is a graph showing the core pressure changes during four cycles of the blank control CO2 gas injection process in Experimental Example 2. DETAILED DESCRIPTION

[0056] The present invention will be further described below in conjunction with embodiments and drawings.

[0057] The raw materials and testing instruments used in the embodiments and comparative examples are all commercially available raw materials and testing instruments commonly used in the art; for example, the fluorinated acrylic acid copolymer was purchased from Shanghai Jianhong Industry and Trade Co., Ltd., and the sources of other raw materials are not described here.

[0058] Example 1

[0059] A modified asphalt particle reinforced oil-based foam system comprises a fluorinated acrylic copolymer, modified asphalt particles and a mixed oil solvent, wherein the structural formula of the fluorinated acrylic copolymer is:

[0060]

[0061] In this embodiment, in Formula I, x is 6, y is 18;

[0062] Modified asphalt particles are prepared by the following method:

[0063] After petroleum asphalt is made into particles with a particle size of 500 mesh, a modifier, an interfacial dispersant, a charge stabilizer and a flexibility regulator are added by spraying, and after stirring at a speed of 20 rpm for 8 hours, the modified asphalt particles are obtained by standing and drying for 24 hours. In this embodiment, the dosage of the modifier, the interfacial dispersant, the charge stabilizer and the flexibility regulator is 5wt%, 10wt%, 2wt% and 10wt% of the mass of the petroleum asphalt, respectively. The modifier is alkyl dimethyl hydroxyethyl quaternary ammonium nitrate, and the interfacial dispersant is prepared by mixing equal masses of non-ionic amino surfactants and cationic diquaternary ammonium salt surfactants. The non-ionic amino surfactant is bisaminoethylaminomethyl p-alkylphenol, and the structural formula is:

[0064]

[0065] In formula II, R1 is a straight chain alkyl group of C4H9;

[0066] The structural formula of cationic diquaternary ammonium salt surfactant is:

[0067]

[0068] In Formula III, R2, R3, R4, and R5 are C1 straight-chain alkyl groups; R6 and R7 are C6 straight-chain alkyl groups; Z - For PO 3- ;

[0069] The charge stabilizer is ethylenediaminetetraacetic acid; the flexibility regulator is polycarbonate.

[0070] In this embodiment, the mixed oil solvent is made by mixing kerosene and dense oil in a volume ratio of 1:9, wherein the density of dense oil is 0.872 g / cm 3 , viscosity is 4.75mPa·s.

[0071] The mass ratio of fluorinated acrylic copolymer, modified asphalt particles and mixed oil solvent is 1:0.2:100.

[0072] The modified asphalt particle enhanced oil-based foam system is prepared by the following method:

[0073] (1) 0.2 wt% (relative to the total mixed oil solvent, the same below) of modified asphalt particles was slowly added to 10 ml of kerosene at a rate of 12 drops / min, and stirred uniformly at 1000 rpm with a magnetic stirrer for 0.5 h, and then 90 ml of dense oil was added and stirred uniformly at the same speed for 1 h;

[0074] (2) subjecting the solution containing solid asphalt particles obtained in step (1) to intermittent ultrasonic dispersion at a power of 600 W for 2 h, wherein the dispersion time is 5 min and the standing time is 60 s, to form a uniform mixed solution in which the modified asphalt particles are fully dispersed and suspended;

[0075] (3) adding 1.0 wt % of fluorinated acrylic acid copolymer to the mixed solution obtained in step (2), and stirring at a low speed of 600 rpm for 0.5 h to form a composite solution; in this step, stirring at a low speed is used to prevent premature foaming;

[0076] (4) The composite solution obtained in step (3) is stirred at a high speed of 8000 rpm for 3 min in a fume hood filled with CO2 gas to obtain a stable modified asphalt particle reinforced oil-based foam.

[0077] Example 2

[0078] A modified asphalt particle reinforced oil-based foam system, which is different from Example 1 in that the mass ratio of the fluorinated acrylic copolymer, the modified asphalt particles and the mixed oil solvent is 1:0.5:100.

[0079] The preparation method is the same as that in Example 1.

[0080] Example 3

[0081] A modified asphalt particle reinforced oil-based foam system, which is different from Example 1 in that the mass ratio of the fluorinated acrylic copolymer, the modified asphalt particles and the mixed oil solvent is 1:1:100.

[0082] The preparation method is the same as that in Example 1.

[0083] Comparative Example 4

[0084] A modified asphalt particle reinforced oil-based foam system, which is different from Example 1 in that the mass ratio of the fluorinated acrylic copolymer, the modified asphalt particles and the mixed oil solvent is 2:1:100.

[0085] Example 5

[0086] A modified asphalt particle reinforced oil-based foam system comprises a fluorinated acrylic copolymer, modified asphalt particles and a mixed oil solvent, wherein the structural formula of the fluorinated acrylic copolymer is:

[0087]

[0088] In this embodiment, in Formula I, x is 3, y is 15;

[0089] Modified asphalt particles are prepared by the following method:

[0090] After petroleum asphalt is made into particles with a particle size of 700 mesh, a modifier, an interfacial dispersant, a charge stabilizer and a flexibility regulator are added by spraying, and after stirring at a speed of 40 rpm for 6 hours, the modified asphalt particles are obtained by standing and drying for 24 hours. In this embodiment, the dosage of the modifier, the interfacial dispersant, the charge stabilizer and the flexibility regulator is 10wt%, 20wt%, 5wt% and 5wt% of the mass of the petroleum asphalt, respectively. The modifier is alkyl dimethyl hydroxyethyl quaternary ammonium nitrate, and the interfacial dispersant is prepared by mixing equal masses of non-ionic amino surfactants and cationic diquaternary ammonium salt surfactants. The non-ionic amino surfactant is bisaminoethylaminomethyl p-alkylphenol, and the structural formula is:

[0091]

[0092] In formula II, R1 is C8H 17 A straight chain alkyl group;

[0093] The structural formula of cationic diquaternary ammonium salt surfactant is:

[0094]

[0095] In Formula III, R2, R3, R4, and R5 are C3 straight-chain alkyl groups; R6 and R7 are C12 straight-chain alkyl groups; and Z - Cl - ;

[0096] The charge stabilizer is ethylenediaminetetraacetic acid; the flexibility regulator is polycarbonate.

[0097] In this embodiment, the mixed oil solvent is made by mixing kerosene and dense oil in a volume ratio of 2:8, wherein the density of dense oil is 0.837 g / cm 3 , viscosity is 1.29mPa·s.

[0098] The mass ratio of fluorinated acrylic copolymer, modified asphalt particles and mixed oil solvent is 1:0.5:100.

[0099] The modified asphalt particle enhanced oil-based foam system is prepared by the following method:

[0100] (1) 0.5 wt% modified asphalt particles were slowly added to 20 ml kerosene at a rate of 12 drops / min, and stirred evenly at 1000 rpm with a magnetic stirrer for 1 h, and then 80 ml dense oil was added and stirred evenly at the same speed for 1.5 h;

[0101] (2) subjecting the solution containing solid asphalt particles obtained in step (1) to intermittent ultrasonic dispersion at a power of 800 W for 1.5 h, wherein the dispersion time is 3 min and the standing time is 40 s, to form a uniform mixed solution in which the modified asphalt particles are fully dispersed and suspended;

[0102] (3) adding 1.0 wt % of fluorinated acrylic acid copolymer to the mixed solution obtained in step (2), and stirring at a low speed of 600 rpm for 1 hour to form a composite solution; in this step, low-speed stirring is used to prevent premature foaming;

[0103] (4) The composite solution obtained in step (3) is stirred at a high speed of 8000 rpm for 5 min in a fume hood filled with CO2 gas to obtain a stable modified asphalt particle reinforced oil-based foam.

[0104] Comparative Example 1

[0105] The oil-based foam system comprises the following raw materials: 100 ml of mixed oil solvent, in which the fluorinated acrylic acid copolymer accounts for 1.0 wt % of the mixed oil solvent.

[0106] The preparation method of the oil-based foam system comprises the following steps:

[0107] (1) 10 ml of kerosene and 90 ml of dense oil were uniformly stirred at 1000 rpm for 1.5 h using a magnetic stirrer to obtain 100 ml of mixed oil solvent;

[0108] (2) adding 1.0 wt % of the fluorinated acrylic acid copolymer to 100 ml of the mixed oil solvent and stirring at a low speed of 600 rpm for 0.5 h to form a uniform mixed solution; in this step, stirring at a low speed is used to prevent premature foaming;

[0109] (3) The mixed solution obtained in step (1) was stirred at 8000 rpm for 3 min in a fume hood filled with CO2 gas to obtain an oil-based foam.

[0110] Comparative Example 2

[0111] The oil-based foam system of this comparative example includes the following raw materials: 100 ml of mixed oil solvent, 0.5 wt % of fluorinated acrylic copolymer, and 0.1 wt % of modified asphalt particles.

[0112] The method for preparing the oil-based foam system foam of this comparative example is the same as the steps in Example 1.

[0113] Comparative Example 3

[0114] The oil-based foam system of this comparative example includes the following raw materials: 100 ml of mixed oil solvent, 0.5 wt % of fluorinated acrylic copolymer, and 0.25 wt % of modified asphalt particles.

[0115] The method for preparing the oil-based foam system foam of this comparative example is the same as the steps in Example 1.

[0116] Comparative Example 4

[0117] The oil-based foam system of this comparative example includes the following raw materials: 100 ml of mixed oil solvent, 0.5 wt % of fluorinated acrylic copolymer, and 0.5 wt % of modified asphalt particles.

[0118] The method for preparing the oil-based foam system foam of this comparative example is the same as the steps in Example 1.

[0119] Comparative Example 5

[0120] The oil-based foam system of this comparative example includes the following raw materials: 100 ml of mixed oil solvent, 1 wt % of fluorinated acrylic acid copolymer, and 0.5 wt % of natural petroleum asphalt particles.

[0121] The method for preparing the oil-based foam system of this comparative example is the same as that of Example 1, except that the particles used are natural petroleum asphalt particles that have not been modified.

[0122] Comparative Example 6

[0123] The oil-based foam system of this comparative example includes the following raw materials: 100 ml of mixed oil solvent, 1 wt% of fluorocarbon cationic surfactant (purchased from Shanghai Jianhong Industrial Co., Ltd., which is a short-chain fluorocarbon surfactant with a total carbon number in the range of 7-9), and 0.5 wt% of modified asphalt particles.

[0124] The difference between the preparation method of the oil-based foam system of this comparative example and the preparation steps of Example 1 is that the surfactant is a commercially available fluorocarbon cationic surfactant.

[0125] Comparative Example 7

[0126] The oil-based foam system of this comparative example is different from that of Example 2 in that the modified asphalt particles are commercially available modified asphalt particles purchased directly from the market (purchased from Dalian Yunhaiyan Asphalt Technology Co., Ltd., and mainly surface-modified by sulfonated groups).

[0127] The preparation method of the oil-based foam system of this comparative example is the same as the steps in Example 1.

[0128] Comparative Example 8

[0129] The difference between this comparative example and Example 1 is that the concentration of the fluorinated acrylic surfactant is 3.0 wt % and the concentration of the modified asphalt particles is 1.5 wt %.

[0130] Experimental Example 1

[0131] The foams provided in Examples 1-5 and Comparative Examples 1-8 were measured for foam expansion ratio and defoaming half-life, wherein the foam expansion ratio was measured by rapidly pouring the foam generated by stirring into a 500 mL measuring cylinder to reduce the influence of the foam precipitate on the reading volume, and reading the foaming volume, foam expansion ratio = foaming volume / base liquid volume (i.e., 100 mL) × 100%; the defoaming half-life was measured by immediately pressing a stopwatch to start timing after stopping stirring and foaming, and stopping timing when the foam volume of the measuring cylinder decays to half of the foaming volume, and this duration is the defoaming half-life.

[0132] The measured data are shown in the following table:

[0133] Table 1 Comparison of oil-based foam performance in different systems

[0134]

[0135] As shown in the data in Table 1, compared with Examples 1-4, the defoaming half-life of the oil-based foam strengthened with modified asphalt particles in Comparative Example 1 is significantly prolonged, and the foam stability is greatly enhanced than that of the oil-based foam without modified asphalt particles. At the same time, the addition of modified asphalt particles has little effect on the foaming ratio, and the strengthened oil-based foam still has good foaming ability.

[0136] From the horizontal comparison of Examples 1-3, it can be seen that when the surfactant concentration is fixed, as the concentration of modified asphalt particles in the foam system increases, the defoaming half-life first increases significantly (the particle concentration increases from 0.2wt% to 0.5wt%), but then the increase is no longer obvious (the particle concentration increases from 0.5wt% to 1.0wt%). This shows that the adsorption amount of modified asphalt particles on the foam gas-liquid interface does not increase continuously.

[0137] By comparing Example 2 and Example 4, it can be seen that when the parameters are changed within the range specified by the technical solution, the effect on the foam performance is small, and the obtained modified asphalt particle-reinforced oil-based foams all achieve good results.

[0138] From the comparison between Examples 1-3 and Comparative Examples 2-4, it can be seen that the optimal concentration of modified asphalt particles is affected by the concentration of surfactants, which indicates that modified asphalt particles require the cooperation of surfactants to achieve adsorption on the interface. The optimal ratio of modified asphalt particles to the fluorinated acrylic copolymer is about 1:2. When the surfactant concentration is constant, after the modified asphalt particles reach saturated interfacial adsorption, further increasing the particle concentration will not improve the foam stability.

[0139] Comparison between Example 2 and Comparative Examples 5 and 7 shows that the modified asphalt particles enhance the oil-based foam and the oil-based foam of natural asphalt particles and commercially available modified asphalt particles. The modified asphalt particles have a significantly better foam stability than the latter two, which indicates that the modified asphalt particles can form a good synergistic interface adsorption effect with the fluorinated acrylic acid copolymer surfactant after modification. When using commercially available modified asphalt particles, although their foaming ratio and defoaming half-life are improved compared with natural asphalt particles, their performance is not as good as the modified asphalt particles.

[0140] From the comparison between Example 2 and Comparative Example 6, it can be seen that the foaming ratio and defoaming half-life of the oil-based foam strengthened by the modified asphalt particles are significantly increased compared with the oil-based foam using the fluorocarbon cationic surfactant. This shows that the fluorinated acrylic copolymer surfactant can form a good synergistic effect with the modified asphalt particles to improve the foam performance, while the use of other types of fluorocarbon surfactants such as fluorocarbon cationic surfactants cannot form a synergistic foam stabilizing effect with the modified asphalt particles.

[0141] From the comparison of Examples 2 and 5 and Comparative Examples 3 and 8, it can be seen that when the concentration ratio of surfactant to modified asphalt particles is fixed, the optimal concentration of the fluorinated acrylic copolymer surfactant is 1wt%-2wt%. Considering the comprehensive cost and effect, the optimal concentration is 1wt%. Continuing to increase its concentration, the foam performance is not significantly improved.

[0142] Experimental Example 2

[0143] Experiment on the effect of foam-assisted CO2 huff and puff.

[0144] Experimental conditions: experimental temperature 70°C, experimental pressure 3MPa.

[0145] Experimental materials: CO2 gas; tight oil (the asphaltene content in crude oil is about 4.5wt%); foaming agent solution; artificial cylindrical long core (Φ2.5×30cm), permeability 35×10 -3 μm 2 .

[0146] Foam system: The foam systems provided in Example 2 and Comparative Example 1 were selected, and a blank control without foam injection was set up.

[0147] Experimental steps:

[0148] (1) Core vacuuming and saturation with tight oil;

[0149] (2) First, the modified asphalt particle enhanced oil-based foam system is injected at a certain pressure, the injection volume is 0.05PV, and the injection pressure is 0.5-1MPa higher than the average core pressure, and then CO2 gas is injected at a volume of 0.20PV, and the injection pressure is 2-3MPa higher than the average core pressure;

[0150] (3) Hold the well to wait for the core pressure to stabilize. Since the injected foaming agent is oil-soluble and can be miscible with the tight oil, the injected CO2 gas dissolves in the tight oil by diffusion under high pressure.

[0151] (4) Depressurization production is carried out, and the CO2 gas precipitated from the dense oil forms modified asphalt particles to strengthen the oil-based foam under the action of the foaming agent solution;

[0152] (5) repeating steps (2) to (4) for multiple rounds of gas huff and puff until the gas huff and puff cycle recovery factor is less than 2.5% of the economic mining recovery factor;

[0153] (6) Monitor core pressure changes and record the recovery factor after each throughput cycle. In addition, separate the asphaltene deposits in the produced oil and determine its content.

[0154] The measured data are as follows:

[0155] Table 2 Comparison of recovery factors in each cycle of gas throughput

[0156] Recovery rate Example 2 Comparative Example 1 Blank control First cycle 19.7% 17.9% 14.3% Second cycle 13.0% 9.7% 6.8% Third cycle 7.8% 5.6% 3.4% Fourth cycle 5.2% 3.9% 2.2% Fifth cycle 4.4% 2.3% - Sixth cycle 3.5% - - Seventh cycle 2.4% - - final 56.0% 39.4% 26.7%

[0157] Table 3 Comparison of asphaltene deposition content in oil produced by different gas throughput

[0158]

[0159]

[0160] As shown in the data in Table 2 and Table 3, the recovery rates of each cycle are compared between Example 2, Comparative Example 1 and the blank control, and it can be seen that the recovery rate of each cycle can be improved by strengthening the oil-based foam system with modified asphalt particles to assist CO2 gas throughput. The recovery rate is significantly improved from the second cycle, and the production cycle is extended. This shows that after multiple throughput cycles, the gas begins to crossflow and the oil-carrying efficiency decreases. After the gas crossflow is blocked by the oil-based foam system strengthened with modified asphalt particles, the gas energy release slows down, and production is carried out in the form of oil-based foam. The rate of decline of the recovery rate in each throughput cycle is controlled, and the production cycle is extended, thereby improving the final recovery rate.

[0161] The oil-based foam system assisted CO2 gas throughput also has a certain ability to block gas cross-flow, but the production cycle is extended for a short time, and the final recovery rate is not as good as in Example 2.

[0162] The blank control only carried out conventional CO2 gas throughput, with a short production cycle and a fast capacity decline, indicating that after multiple rounds of throughput, gas breakthrough occurred rapidly, the affected area was small, and the efficiency of tight oil utilization was low.

[0163] The final recovery rate of Example 2 is 56.0%, which is 2.10 times that of the blank control, while the final recovery rate of Comparative Example 1 is 39.4%, which is 1.47 times that of the blank control.

[0164] Comparison of the asphaltene deposition content of the produced oil in Example 2, Comparative Example 1 and the blank control shows that the asphaltene deposition in the produced oil can be effectively reduced by strengthening the oil-based foam system with modified asphalt particles to assist CO2 gas throughput. This shows that after the modified asphalt particles are injected, the various additives adsorbed on their surface diffuse and transfer to the surface of the asphaltene precipitated from the formation, achieving in-situ modification of the formation asphaltene, so that it remains in the core and continues to play a role in stabilizing the foam, reducing the asphaltene deposition in the final produced oil. The asphaltene deposition content of the produced oil in Comparative Example 1 and the blank control is significantly higher than that in Example 2.

[0165] Comparison of the pressure changes in each cycle between Example 2, Comparative Example 1 and the blank control shows that Figure 1 As shown, in Example 2, the modified asphalt particles enhanced the oil-based foam system to assist CO2 gas throughput. As the throughput cycle increases, the injection pressure required for the next throughput cycle is higher than that of the previous cycle. This indicates that after the foaming agent solvent is injected, the modified asphalt particles can be retained in the core pores, play a role in stabilizing the oil-based foam, further inhibit gas crosstalk, and slow down energy release.

[0166] like Figure 2 As shown, in Comparative Example 1, the oil-based foam system assisted CO2 gas throughput. As the throughput cycle increased, the injection pressure of each cycle could be basically maintained unchanged, indicating that the oil-based foam has a certain ability to inhibit gas cross-flow.

[0167] like Figure 3 As shown in the figure, in the blank control, as the CO2 gas throughput cycle increases, the injection pressure required for the next throughput cycle gradually decreases compared with the previous cycle, indicating that after multiple rounds of gas throughput, a gas crossflow channel is gradually formed, the resistance to the injected gas is reduced, and the injection pressure decreases.

[0168] Experimental Example 3

[0169] Surfactants reduce interfacial tension experiment

[0170] The oil-gas interfacial tension was measured using an interfacial rheometer (Tracker-H, Techlis, France), which mainly consisted of a light source, a propeller, a syringe, a sealed kettle with an observation window, a camera, and an image acquisition and data analysis system.

[0171] During the experimental measurement, the propeller is controlled by the computer to move downward, and the oil solution to be tested is bulged into droplets at the needle of the syringe. When a nearly pear-shaped droplet is generated with a stable time of 4-6 minutes, a high-definition camera is used to collect real-time photos of the droplet morphology on the computer, and the interfacial tension is calculated based on the area, volume and other data of the droplet. Before the measurement, the sealed cylinder is filled with CO2, with the liquid phase as the inner phase and the gas as the outer phase.

[0172] The oil-based foam system uses the oil-based foam system provided by Examples 1-3 and the oil-based foam system provided by Comparative Examples 1 and 6.

[0173] In addition, a blank control was set up in which neither the fluorinated acrylic copolymer nor the modified asphalt particles were added.

[0174] Table 4 Comparison of oil-gas interfacial tension in different systems

[0175]

[0176] As shown in the data of Table 4, by comparing Examples 1-3, Comparative Example 1 and the blank control, it can be seen that the fluorinated acrylic copolymer has the ability to reduce the oil-gas interfacial tension, and the modified asphalt particles can further reduce the oil-gas interfacial tension on this basis. This shows that the modified asphalt particles can cooperate with the fluorinated acrylic copolymer to reduce the oil-gas interfacial tension and improve the foam stability.

[0177] Comparison between Example 2 and Comparative Example 6 shows that the effect of reducing oil-gas interfacial tension using the existing commercially available fluorocarbon cationic surfactant and modified asphalt particles is poor because the surfactant has a short hydrocarbon chain, 7-9 carbon atoms, weak molecular non-polarity, insufficient affinity for oil, and therefore is difficult to play a role in the oil phase. Fluorinated acrylic acid copolymer is not only a surfactant, but also a polymer. Its long hydrocarbon chain structure gives it a strong affinity for oil, allowing it to play a role in the oil phase system.

[0178] A lateral comparison of Examples 1-3 shows that, at a certain fluorinated acrylic copolymer concentration, continuously increasing the concentration of modified asphalt particles does not lead to a continuous decrease in the oil-gas interfacial tension. When the concentration ratio of modified asphalt particles to fluorinated acrylic copolymer is 1:2, the effect of reducing the oil-gas interfacial tension is optimal.

Claims

1. A modified asphalt particle enhanced oil-based foam system, characterized in that: It includes fluorinated acrylic copolymer, modified asphalt particles and mixed oil solvent, and the mass ratio of fluorinated acrylic copolymer, modified asphalt particles and mixed oil solvent is in the range of (1-2):(0.2-1):100; The structural formula of fluorinated acrylic copolymer is as follows: In formula I, x is 3-6, y is 15-20; Modified asphalt particles are prepared by the following method: After the petroleum asphalt is made into particles with a particle size of 500-700 mesh, a modifier, an interface dispersant, a charge stabilizer and a flexibility regulator are added by spraying, and after stirring at a speed of 20rpm-40rpm for 6-8h, the modified asphalt particles are obtained by standing and drying for 24h; the dosage of the modifier, the interface dispersant, the charge stabilizer and the flexibility regulator is 5wt%-10wt%, 10wt%-20wt%, 2wt%-5wt% and 5wt%-10wt% of the mass of the petroleum asphalt respectively; The foaming ratio of the foam system is 325%-355%, and the defoaming half-life is 61min-90min.

2. The modified asphalt particle enhanced oil-based foam system according to claim 1, characterized in that: The mass of the fluorinated acrylic copolymer is twice that of the modified asphalt particles.

3. The modified asphalt particle enhanced oil-based foam system according to claim 1, characterized in that: The modifier is selected from at least one of dodecyltrimethylammonium salt, didodecyltrimethylammonium salt or dodecyldimethylbenzylammonium salt; The interfacial dispersant is selected from nonionic amino surfactants and / or cationic diquaternary ammonium salt surfactants, The charge stabilizer is ethylenediaminetetraacetic acid. The flexibility regulator is at least one of polypropylene, polycarbonate or polyetheretherketone, The nonionic amino surfactant is bisaminoethylaminomethyl p-alkylphenol, and its structural formula is as follows: In formula II, R1 is a C4-C8 straight chain alkyl group; The structural formula of cationic diquaternary ammonium salt surfactant is as follows: In Formula III, R2, R3, R4, and R5 are C1-C3 straight chain alkyl groups; R6 and R7 are C6-C 12 A straight chain alkyl group; Z - For halogen ions or PO3 - Any of .

4. The modified asphalt particle enhanced oil-based foam system according to claim 1, characterized in that: The mixed oil solvent is composed of light oil and dense oil, wherein the light oil is selected from kerosene or diesel, and the ratio of the light oil to the dense oil is 1:(4-9).

5. The method for preparing the modified asphalt particle enhanced oil-based foam system according to any one of claims 1 to 4, characterized in that: The steps include: S1. Adding modified asphalt particles into light oil and stirring for the first time, adding dense oil for the second stirring and ultrasonic dispersion to obtain a modified asphalt particle suspension; S2. Add the fluorinated acrylic copolymer to the modified asphalt particle suspension, and stir at a low speed to obtain a composite solution; S3. In a CO2 / N2 / deoxygenated air atmosphere, the compound solution is stirred at high speed to obtain a modified asphalt particle-enhanced oil-based foam system.

6. The preparation method according to claim 5, characterized in that: In step S1, the first stirring condition is stirring at a speed of 1000 rpm for 0.5 h-1 h; the second stirring condition is stirring at a speed of 1000 rpm for 1 h-1.5 h; In step S1, the ultrasonic dispersion condition is intermittent dispersion at a power of 600W-800W for 1.5h-2h, and the intermittent dispersion process is cyclically carried out in the order of dispersion-intermittence, wherein the dispersion time is 3min-5min and the intermittent time is 40s-60s.

7. The preparation method according to claim 5, characterized in that: In step S2, the low-speed stirring condition is stirring at a rotation speed of 600 rpm for 0.5 h-1 h.

8. The preparation method according to claim 5, characterized in that: In step S3, the high-speed stirring condition is stirring at a rotation speed of 8000 rpm for 3 min-5 min.

9. Use of the modified asphalt particle-enhanced oil-based foam system according to any one of claims 1 to 4 or the modified asphalt particle-enhanced oil-based foam system prepared by the preparation method according to any one of claims 5 to 8 in gas throughput in tight oil reservoirs.

10. The use according to claim 9, characterized in that The asphaltene content of crude oil in tight oil reservoirs ranges from 3.5wt% to 6.0wt%.

Citation Information

Patent Citations

  • Complex heavy oil reservoir oil solubility foaming agent intensified mixed gas huff-puff experimental equipment and application method thereof

    CN108071390A

  • A fluorosilicone surfactant containing monoperfluorooctyl and an oil-based foam displacement agent

    CN108671850B

  • Silicofluoride surfactant containing double perfluorooctyl groups and oil-based foam oil-displacing agent

    CN108690592A

  • Silicofluoride surfactant containing three perfluorooctyl groups and oil-based foam oil-displacing agent

    CN108690593A

  • High-temperature-resistant oil-based foam drilling fluid and preparation method thereof

    CN114437683A